1981
DOI: 10.4039/ent113223-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Black Flies (Diptera: Simuliidae) of the Souris River, Manitoba as a Basis for Control Strategy

Abstract: Can. Ent. 113: 223-234 (1981)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Porter (1979, 1981) demonstrated that the size of larvae of S. vittatum can be affected by feeding and temperature under laboratory conditions. Ross and Merritt (1978) and Westwood and Brust (1981) found seven instars in S. vittatum, while Colbo and Porter (1979) reported eight instars. Since this nominal species is composed of several cytospecies, the different results could be a reflection of the inadequacy of species identification based on gross morphology.…”
Section: Resultsmentioning
confidence: 98%
“…Porter (1979, 1981) demonstrated that the size of larvae of S. vittatum can be affected by feeding and temperature under laboratory conditions. Ross and Merritt (1978) and Westwood and Brust (1981) found seven instars in S. vittatum, while Colbo and Porter (1979) reported eight instars. Since this nominal species is composed of several cytospecies, the different results could be a reflection of the inadequacy of species identification based on gross morphology.…”
Section: Resultsmentioning
confidence: 98%
“…Published records for southem Manitoba are fewer than for the north and the only notable paper is one by Westwood and Brust (1981). These authors reported the occurrence of 10 species collected while investigating the prospects for blackfly control on the Souris river (a southern tributary of the Assiniboine that enters Manitoba from North Dakota).…”
Section: The Manitoban Background For Simuliidaementioning
confidence: 90%
“…Other records: Churchill (Shewell and Fredeen, 1958 [1983]. The Pembina River, where pupae were found, has much the same character as its Souris River tributary, a breeding site described by Westwood and Brust (1981) with interspersed turbulent and slow meandering stretches, much sediment and little emergent vegetation. Other records: Gillam (Shewell, , 1958also CNC); Red River (Shewell, 1958); Souris River (Shewell, 1958;Westwood and Brust, 1981; also ECUM); Aweme and 5 miles SW of Shilo (CNC).…”
Section: Cnephia Dacotensis (Dyar and Shannon)mentioning
confidence: 99%
See 2 more Smart Citations